2009
DOI: 10.1007/s11802-009-0425-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of preparative separation and purification of total polyphenols from Sargassum tenerrimum by column chromatography

Abstract: Polyphenols from the ethanol extracts of Sargassum tenerrimum (ST) with potent antiallergic effects were studied to optimize separation process through column chromatography. The adsorption and desorption characteristics of three widely used adsorbents: macroporous resin, silica gel, and polyvinylpolypyrrolidone (PVPP), were critically evaluated respectively and studied for the optimization of preparative separation of polyphenols. Static operations on these adsorbents showed that macroporous resin had the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The PI3K-Akt signaling pathway is aberrantly activated during the occurrence and progression of certain cancers. The two most extensively elucidated mechanisms underlying PI3K-Akt activation in human cancer involve receptor tyrosine kinase stimulation and somatic mutations in specific components of signaling pathways ( 41 ). Augmentation and facilitation of the PI3K-Akt pathway may exert a detrimental impact on cancer therapy; hence, inhibition of PI3K could impede cancer development ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway is aberrantly activated during the occurrence and progression of certain cancers. The two most extensively elucidated mechanisms underlying PI3K-Akt activation in human cancer involve receptor tyrosine kinase stimulation and somatic mutations in specific components of signaling pathways ( 41 ). Augmentation and facilitation of the PI3K-Akt pathway may exert a detrimental impact on cancer therapy; hence, inhibition of PI3K could impede cancer development ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SPE procedures, such as macroporous resins, silica gel and dispersants, are safer alternatives. Haider, Zhenxing, Hong, and Jamil (2009) demonstrated that macroporous resins are better than silica gel and polyvinylpolypyrrolidone in adsorbing/desorbing phlorotannins. Later, J.…”
Section: Phlorotannins Separationmentioning
confidence: 99%
“…The incidence and mortality rates of lung cancer are the highest among all cancer types, with these rates being the second highest among females [6]. Studies have shown that the polyphenols from green tea, apples, seaweed, and rice husks can help in inhibiting lung cancer in vitro or in vivo [7,8].…”
Section: Introductionmentioning
confidence: 99%